2004
DOI: 10.1002/jmv.20174
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of selection of K65R and Q151M mutations in HIV‐2 infected patients receiving nucleoside reverse transcriptase inhibitors containing regimen

Abstract: The objective of the study was to determine retrospectively which substitutions in the reverse transcriptase (RT) gene are selected in vivo during nucleoside RT inhibitors (NRTI) containing regimen in HIV-2 infected subjects. Thirty-four HIV-2 patients having received NRTI-containing regimen with available specimens and amplifiable RT gene were studied. Analyses of RT gene were undertaken after a median NRTI exposure of 51 months (range: 5-128). Mutations at positions known to be involved in HIV-1 resistance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…Wild-type HIV-2 RT contains Ser instead of Thr at position 215, and only one nucleotide change is needed to obtain the substitution S215Y. However, Q151M emerges as the major AZT resistance mutation in HIV-2 RT, whereas TAMs are relatively uncommon in HIV-2-infected patients (72)(73)(74). Molecular modeling studies suggested that several amino acid differences around the putative ATP binding site of HIV-2 RT in comparison with the HIV-1 RT could account for these differences (75).…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type HIV-2 RT contains Ser instead of Thr at position 215, and only one nucleotide change is needed to obtain the substitution S215Y. However, Q151M emerges as the major AZT resistance mutation in HIV-2 RT, whereas TAMs are relatively uncommon in HIV-2-infected patients (72)(73)(74). Molecular modeling studies suggested that several amino acid differences around the putative ATP binding site of HIV-2 RT in comparison with the HIV-1 RT could account for these differences (75).…”
Section: Discussionmentioning
confidence: 99%
“…In regard to the K65R mutation, several clinical studies reported a high frequency of the mutation in NRTI-treated patients infected with HIV-2 (13,14), whereas in other studies K65R was rarely observed (34)(35)(36). In addition, in vitro, the selection of K65R in HIV-2 is not common (37,38).…”
Section: Figmentioning
confidence: 99%
“…In HIV-2 patients failing therapy, V111I was previously reported to be coselected with mutation Q151M (14,15,20). Mutation Q151M alone was suggested to confer resistance to d4T and ABC, whereas resistance to other NRTIs would involve the coselection of V111I (20).…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations